Digital Gamification for Vocabulary Growth: Evaluating Educaplay for EFL Learners in a Boarding School Setting - Aidil Akbar Rahman; Muajiz Muallim (Studies in Language, Education, and Culture (SeLEC), 2025)
This study examines the use of Educaplay, a gamified digital platform, to enhance vocabulary acquisition among EFL students at Zubdatul Asrar NU Boarding School in Parepare. Recognizing the limitations of traditional vocabulary instruction, the research explores how interactive, game-based learning can support engagement and retention. A pre-experimental one-group pretest-posttest design was employed with 42 randomly selected students. Vocabulary tests were administered before and after six sessions using Educaplay activities, and a student questionnaire was used to assess learner perceptions. The results showed a significant improvement in vocabulary mastery, with mean scores increasing from 55.71 to 94.48. Questionnaire data revealed high levels of student motivation and satisfaction with the learning process. These findings suggest that digital gamified tools like Educaplay can effectively support vocabulary development in EFL contexts, offering an engaging and inclusive alternative to traditional methods.